Overcoming the Past-endorsement Criterion: Toward a Transparency-Based Mark of the Mental - Piredda, Giulia; Di Francesco, Michele (Frontiers in Psychology, 2020)
Starting from the discussion on the original set of criteria advanced by Clark and Chalmers (1998) meant to avoid the overextension of the mind, or the so-called cognitive bloat, we will sketch our solution to the problem of criteria evaluation, by connecting it to the search for a mark of the mental. Our proposal is to argue for a “weak conscientialist” mark of the mental based on transparent access, which vindicates the role of consciousness in defining what is mental without, however, identifying the mental with the conscious. This renovated link between mind and consciousness, spelled out through the concept of transparency, further develops some of our previous work on the topic (Di Francesco, 2007; Di Francesco and Piredda, 2012) and is partially inspired by Horgan and Kriegel (2008).